(untitled) (Medico Legal Update, 2021)
Tuberculosis (TB) is an infectious disease that is caused by Mycobacterium tuberculosis, which attacks various organs, especially lungs. This disease must be treated immediately before it causes complications even death. The number of TB cases in Indonesia was 420,994 cases in 2017. Lack of adherence against TB treatment still becomes an obstacle of global health, and mobile phone-based interventions have potential to solve this problem. Furthermore, this research aimed at investigating the influence of telenursing against adherence to anti-TB treatment toward patient with tuberculosis. This research was conducted in Bima City, West Nusa Tenggara Province, Indonesia which consisted of 3 (three) Public Health Centers. Method of this research was experimental anddesign in this research used quasi experimental design (One group PretestPosttest Design). Moreover, results of this research showed that TB respondents before being treatedby telenursing who were in category of moderate adherence were 14 respondents (23.3%), meanwhile, in category of poor adherence were 46 respondents (76.7%). After being treatedby telenursing, TB respondents who were in category of high adherence were 60 respondents (100%). Test through SPSS was obtained a significant result which was 0.001 for intervention with a significance level of 0.05. Because p value was <0.05, then Ho was rejected, which meant that there was a significant difference in results between before and after being treated by telenursing.